The Effect of CSR, Tunneling Incentive, Fiscal Loss Compensation, Debt Policy, Profitability, Firm Size to Tax Avoidance - Lestari, Jihan; Solikhah, Badingatus (UNIVERSITAS NEGERI SEMARANG, 2019)
The purpose of this research is to analyze the effect of variables of CSR, tunneling incentive, fiscal loss compensation, debt policy, profitability, and firm size on tax avoidance. The population of this research are 143Manufacturing Companies Listed on BEI In 2012-2016. This research used purposive sampling with a sample of 24 companies. The total sample unit is 120 samples. The analytical tool used in this research is multiple linear regressions. The collected data then analyzed with classic assumption test the hypothesis test by means of SPSS 21. The result of this research is tunneling incentive, fiscal loss policy, and profitability have positive and significant effect to tax avoidance. Debt policies have a negative and significant effect on tax avoidance. Meanwhile, CSR and firm size does not affect tax avoidance. Based on the results of the study it can be concluded that only tunneling incentive, fiscal loss compensation, and profitability are able to increase tax avoidance.